2020
DOI: 10.3390/catal10090984
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Co Oxidation State in Ba0.5Sr0.5Co0.8Fe0.2O3-δ by Flame Spray Synthesis Towards High Oxygen Evolution Reaction Activity

Abstract: The perovskite-type oxide Ba0.5Sr0.5Co0.8Fe0.2O3-δ (BSCF) is known as a highly active and stable oxygen evolution reaction (OER) electrocatalyst composited out of non-noble metals. The possibility of using the scalable flame spray synthesis (FSS) technique for the production of BSCF nanoparticles intensified the interest in this material for a future application in an alkaline water electrolyzer. A possible scale-up would require the optimization of the synthesis parameters to maximize the production rate. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…The great capability of BSCF to create a self-assembled, stable, and highly active oxyhydroxide layer under OER conditions was ascribed to the great flexibility of BSCF to accommodate oxygen vacancies. Indeed, BSCF with Co in a reduced oxidation state, and thus with a high amount of oxygen vacancies, has proved higher OER activity compared to the same perovskite composition with Co cations in a more oxidized state (i.e., with higher oxygen content). ,,, More generally, considering the results of different studies on various perovskites, the oxygen vacancy formation energy/content seems to be an established indicator of high OER activity that has a role in the LOER mechanism. ,,,, Mefford et al, for the La 1– x Sr x CoO 3– δ series, found a direct correlation between Co–O bond covalence, oxygen vacancies and diffusivity, and OER activity. The authors reported that for the La 1– x Sr x CoO 3– δ series, the higher the covalent character of the Co–O bond the higher the vacancy concentration, and also the OER activity.…”
Section: Reaction Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The great capability of BSCF to create a self-assembled, stable, and highly active oxyhydroxide layer under OER conditions was ascribed to the great flexibility of BSCF to accommodate oxygen vacancies. Indeed, BSCF with Co in a reduced oxidation state, and thus with a high amount of oxygen vacancies, has proved higher OER activity compared to the same perovskite composition with Co cations in a more oxidized state (i.e., with higher oxygen content). ,,, More generally, considering the results of different studies on various perovskites, the oxygen vacancy formation energy/content seems to be an established indicator of high OER activity that has a role in the LOER mechanism. ,,,, Mefford et al, for the La 1– x Sr x CoO 3– δ series, found a direct correlation between Co–O bond covalence, oxygen vacancies and diffusivity, and OER activity. The authors reported that for the La 1– x Sr x CoO 3– δ series, the higher the covalent character of the Co–O bond the higher the vacancy concentration, and also the OER activity.…”
Section: Reaction Mechanismsmentioning
confidence: 99%
“…Indeed, BSCF with Co in a reduced oxidation state, and thus with a high amount of oxygen vacancies, has proved higher OER activity compared to the same perovskite composition with Co cations in a more oxidized state (i.e., with higher oxygen content). 92,103,117,118 More generally, considering the results of different studies on various perovskites, the oxygen vacancy formation energy/ content seems to be an established indicator of high OER activity that has a role in the LOER mechanism. 102,103,110,111,119−121 Mefford et al, 102 for the La 1−x Sr x CoO 3−δ series, found a direct correlation between Co−O bond covalence, oxygen vacancies and diffusivity, and OER activity.…”
Section: Acs Catalysismentioning
confidence: 99%
“…In these syntheses, the use of high-temperature calcination for prolonged periods to form a crystalline phase inevitably leads to the agglomeration of particles regardless of the synthesis parameters that can be tuned, ultimately resulting in limited catalytic activity, in particular, based on a mass consideration. Downsizing the BSCF particle to tens or hundreds of nanometers can significantly boost the mass activity, often facilitated by special synthesis techniques, for example, flame spray pyrolysis. ,,, By controlling the spray pyrolysis conditions, the transition metal oxidation state and the oxygen-deficient level of BSCF can be tailored, which in turn impacts its capability to self-reconstruct and hence catalyze the OER . Constructing BSCF nanostructures with porosity represents another means to increase the mass activity, which is usually realized by templating methods. , Using a tetraethoxysilane-templated approach, Yang et al obtained a hierarchically porous BSCF with a >60-fold increase in BET surface area and a >5-fold increase in OER mass activity compared to the nonporous BSCF .…”
Section: Energy Storage and Conversion Applicationsmentioning
confidence: 99%
“…Downsizing the BSCF particle to tens or hundreds of nanometers can significantly boost the mass activity, often facilitated by special synthesis techniques, for example, flame spray pyrolysis. 24,67,146,150 By controlling the spray pyrolysis conditions, the transition metal oxidation state and the oxygendeficient level of BSCF can be tailored, which in turn impacts its capability to self-reconstruct and hence catalyze the OER. 150 Constructing BSCF nanostructures with porosity represents another means to increase the mass activity, which is usually realized by templating methods.…”
Section: Energy Storage and Conversion Applicationsmentioning
confidence: 99%
See 1 more Smart Citation